Attitudes Towards Code-Switching Involving Arabic in a Multilingual Situation – The Case of Accra - Abdullah, Bulukia (AUC Knowledge Fountain, 2021)
This thesis investigated Ghanaians' attitudes towards code-switching involving Arabic and Ghanaian languages in a highly formal religious setting like the Friday sermon. It aimed to offer the perception and beliefs of Ghanaian Islamic scholars and Ghanaian Muslims towards code-switching from Arabic to the local Ghanaian languages and vice versa. Data from 69 Ghanaian Muslims and 5 Islamic scholars from two different mosques in Accra, Ghana, were examined to achieve this purpose. The data was collected through web-based questionnaires, interviews, a Matched-guise test. The study's findings showed that Ghanaians had favorable attitudes towards code-switching from Arabic to Ghanaian languages (GLs) and from GLs to Arabic. Code-switches from Arabic to GLs, were seen as appropriate and approved in this highly formal setting. In general, the participants viewed it as a medium by which Islamic scholars get to the level of their congregation, create solidarity among members, and make the speech easier for the audience to understand. On the other hand, alternating from GLs to Arabic was viewed as demonstrating one's Islamic knowledge, giving credibility to the message and thus, showing its importance. These findings indicate that switching from Arabic to GLs was Ghanaians' efforts to maintain their indigenous languages in this extremely formal context. Switching from GLs to Arabic served the purpose of referencing and symbolic to the Islamic religious faith.